The Athenian Standards Decree: The Aphytis Fragments - Hatzopoulos Miltiades Β. (Tekmeria, 2016)
The discovery and publication in 2003 of a second fragment from Aphytis (Chalkidike) of the Athenian Standards Decree imposed a reconsideration of its date, scope and relations to the other copies of the same document respectively located in Siphnos, Smyrna, Cos, Odessa and Hamaxitos. The restored, thanks to the joining of its two fragments, Aphytis copy, now forty lines long, emerges as the most significant that we possess. It is the longest and most complete version. In combination with other new discoveries, such as the Hamaxitos fragment, or with recent work on other long-known relevant documents, it enables us to obtain throughout the text several improved readings. Its last portion in particular can now be entirely restored with almost absolute certainty. It gives the end of the Standards Decree text, at least in one of its versions. This can be extensively compared to the other extant versions, enabling us to attempt a comprehensive interpretation of the variations observed between them. Its spellings as well as its tone and content offer valuable clues concerning its date, the revision of which affects that of a number of other very important fifth-century Athenian inscriptions. Finally, it calls for a more general reflection on the relative weight that should be attributed to formal and historical arguments respectively in dating archaeological finds.